Transcriptional Profile of Helicobacter pylori Virulence Genes in Patients with Gastritis and Gastric Cancer - Manouchehr Ahmadi Hedayati; Saeed Salavati (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Numerous molecular epidemiology studies have been performed about the frequency of Helicobacter pylori virulence genes in patients with H. pylori infection so far. This study was conducted to detect transcriptional profile by cDNA of H. pylori virulence genes in gastric biopsy samples of gastritis and gastric carcinoma patients. Materials and Methods. In a case-control study, based on the prevalence of gastritis and gastric cancer in Sanandaj city during 2018 and 2019, 23 and 11 gastric antral biopsy samples with H. pylori infection were collected from gastritis and gastric carcinoma patients by the consecutive and available sampling method. Pathological characters, including tumor grades and tumor areas for gastric carcinoma biopsy samples prepared from gastric cancer areas, were determined by the pathologist. Total RNA of gastric antral biopsy samples was extracted, and their cDNA was synthesized by TaKaRa kit. H. pylori virulence genes’ cDNA using specific primers and PCR was detected. This study’s results were analyzed by SPSS version 25 and statics chi-square tests for determination of relationship and correlation between cDNAs of H. pylori transcriptional profile and clinical outcomes of H. pylori infection, including gastritis, gastric carcinoma, tumor grades, and tumor area. Results. The positive statistical correlations were observed between transcripts of cagA, cagA-EPIYAC, cagE, and cagY genes and H. pylori infection clinical outcomes (P<0.05). Conclusion. Detection of the H. pylori virulence genes’ cDNA in gastric biopsy samples can help provide the prognosis of clinical outcomes.